divide f(x)=-x^2+2x^3-2x-7 by g(x)=-2+x
Answers
Answered by
11
Heya !!
X - 2 = 0
X = 2
F ( x ) = -X² + 2X³ - 2X - 7
=> 2X³ - X² - 2X - 7
F (2) = 2 × (2)³ - (2)² - 2 × 2 - 7
=> 2 × 8 - 4 - 4 - 7
=> 16 - 15
=> 1.
F(2) = 1
X - 2 = 0
X = 2
F ( x ) = -X² + 2X³ - 2X - 7
=> 2X³ - X² - 2X - 7
F (2) = 2 × (2)³ - (2)² - 2 × 2 - 7
=> 2 × 8 - 4 - 4 - 7
=> 16 - 15
=> 1.
F(2) = 1
qwertyuiop89:
hi
Answered by
7
Hey mate!
Here's ur answer dear:-)
__________________________________________
Given: g(x)= -2+x=0 -- x = 2
p(x) = -x^2+2x^3-2x-7
p(2)= -(2)^2+2(2)^3-2(2)-7
p(2) = - 4 + 16 - 4 -7
p(2) = 16-15
p(2) = 1
_________________________________________
HOPE IT HELPS!
♥♥
Here's ur answer dear:-)
__________________________________________
Given: g(x)= -2+x=0 -- x = 2
p(x) = -x^2+2x^3-2x-7
p(2)= -(2)^2+2(2)^3-2(2)-7
p(2) = - 4 + 16 - 4 -7
p(2) = 16-15
p(2) = 1
_________________________________________
HOPE IT HELPS!
♥♥
Similar questions
English,
8 months ago
Computer Science,
8 months ago
Computer Science,
8 months ago
Physics,
1 year ago
Math,
1 year ago
Math,
1 year ago